Desain Kontrol Motor Brushless Direct Current (BLDC) Menggunakan Boost Converter - Hasan, Ervina; Daud, Muhammad; Yusdartono, Habib Muharry; Kartika, Kartika (Jetri : Jurnal Ilmiah Teknik Elektro, 2023)
Technological developments are increasingly rapid, especially in the field of transportation, especially in electric vehicles, which are triggered by the increasing scarcity of fossil fuels. One of the propulsion engines that are widely used in electric vehicles is the brushless direct current (BLDC) motor because this motor has high torque, constant speed and is easy to regulate. This study aims to design a BLDC motor control using a boost converter as a voltage increaser and using a PID controller as a motor speed controller to keep it constant. In this study, the motor speed is simulated with an input value of 3000 rpm and then a DC voltage of 310 Vdc is given. The results showed that the motor speed regulation using a boost converter can rotate constant. The boost converter as a voltage booster is able to increase the Vin 220 Vdc voltage to a more 10% Vout, which is 242.3 V. Keywords: Brushless Direct Current (BLDC) Motor, Boost Converter, PID